Unified modeling of photothermal and photochemical damage - Denton, Michael L.; Clark, Clifton D.; Noojin, Gary D.; West, Haleigh; Stadick, Allison; Khan, Taufiquar (Frontiers in Ophthalmology, 2024)
Correlating damage outcomes to a retinal laser exposure is critical for diagnosis and choosing appropriate treatment modalities. Therefore, it is important to understand the causal relationships between laser parameters, such as wavelength, power density, and length of exposure, and any resulting injury. Differentiating photothermal from photochemical processes in an in vitro retinal model using cultured retinal pigment epithelial cells would be a first step in achieving this goal. The first-order rate constant of Arrhenius has been used for decades to approximate cellular thermal damage. A modification of this equation, called the damage integral (Ω), has been used extensively to predict the accumulation of laser damage from photothermal inactivation of critical cellular proteins. Damage from photochemical processes is less well studied and most models have not been verified because they require quantification of one or more uncharacterized chemical species. Additionally, few reports on photochemical damage report temperature history, measured or simulated. We used simulated threshold temperatures from a previous in vitro study to distinguish between photothermal and photochemical processes. Assuming purely photochemical processes also inactivate critical cellular proteins, we report the use of a photothermal Ω and a photochemical Ω that work in tandem to indicate overall damage accumulation. The combined damage integral (ΩCDI) applies a mathematical switch designed to describe photochemical damage relative to wavelength and rate of photon delivery. Although only tested in an in vitro model, this approach may transition to predict damage at the mammalian retina.